Metal-Organic Frameworks-Derived FeS-Co9S8/NCA Porous Aerogel Electrocatalyst as a High-Performance Cathode for Zinc-Air Batteries - Qin, Yunong (Langmuir : the ACS journal of surfaces and colloids, 2024)
Herein, a novel strategy to establish a porous FeS-Co9S8/carbon aerogel (FeS-Co9S8/NCA) electrocatalyst for oxygen evolution reaction (OER) is fabricated via applying a green biomass carrageenan sulfuration method to CoFe-metal-organic frameworks (MOFs). The FeS-Co9S8/NCA exhibits optimized catalytic activity toward the OER with a lower overpotential of 322 mV, which is overmatched to the majority of transition metal sulfides (TMSs), as well as lifted long-term durability without evident variation in the LSV curves after 3000 cycles. Rechargeable liquid zinc-air battery (ZAB) assembled with FeS-Co9S8/NCA as the OER catalyst indicated a maximum power density of 176 mW cm-2 and superior cycling stability without raised polarization even after 48 h, outperforms commercial RuO2-based ZAB. Furthermore, the flexible solid-state ZAB built with FeS-Co9S8/NCA also demonstrated outdistance properties and bendability. The excellent performance stems from the hierarchical porous aerogel structure, which offers a multiscale mass/electron transport channel, together with the interfacial synergy effect between FeS and Co9S8, which serves as the active site of the OER reaction. Thus, this work instituted a novel strategy for obtaining both clean and efficient transition metal sulfide electrocatalysts for the OER reaction and an environmentally friendly biomass material-based sustainable electrocatalyst